SOME WOOD PROPERTIES OF MELIAa AZEDARACH L. TREES GROWN IN DUHOK PROVINCE - & et al., Abdulqader (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Melia azedarach L. was introduced into Kurdistan region and planted as an ornamental tree at the nurseries, parks and streets. This study investigated the quality of wood of 9 year old M. azedarach trees grown in Duhok province. Samples of wood from five trees were taken at breast height diameter; and their wood quality was studied in terms of morphological, physical and anatomical properties. Results revealed that the values of morphological properties were: the Heartwood percentage (69.01%), Sapwood percentage (12.93%), Bark percentage (8.06%) and Annual Ring Width (7.74mm). While, the values of the physical properties were: specific gravity (0.42), basic density of wood (0.36g/cm3), annual ring growth width (7.74cm), moisture content (44.46%), maximum moisture content (208.36%), volumetric shrinkage (13.18%), volumetric swelling (16.25%), fiber saturation point (36.34%), cell wall (28.05%) and porosity (71.94%). The values of anatomical properties were: fiber length (0.792 mm), fiber diameter at the mid- point of the fiber (17.75 μm), fiber double cell wall thickness (9.67 μm), fiber lumen width (8.07μm), runkel ratio (1.55), flexibility ratio (47.17), slenderness ratio (47.58), vessel length (241.57μm), vessel diameter at the mid- point of the vessel (169.09μm), and vessel lumen diameter (158.26μm). All properties showed a significant variation from pith to bark and between the trees. The results equip a basis for determining management planning opportune to production wood of M. azedarach plantation trees in Kurdistan region. Also M. azedarach is characterized by low strength resistance and perhaps low pulping production too, therefore according to its low wood quality for some properties, is not recommended for structural purposes. While anatomical properties, showed medium values of fiber dimensions which could be used for production of special type of paper